Limitations and risks of machine ethics - Brundage, Miles (Journal of experimental & theoretical artificial intelligence, 2014)
Many authors have proposed constraining the behaviour of intelligent systems with 'machine ethics' to ensure positive social outcomes from the development of such systems. This paper critically analyses the prospects for machine ethics, identifying several inherent limitations. While machine ethics may increase the probability of ethical behaviour in some situations, it cannot guarantee it due to the nature of ethics, the computational limitations of computational agents and the complexity of the world. In addition, machine ethics, even if it were to be 'solved' at a technical level, would be insufficient to ensure positive social outcomes from intelligent systems.